Synthesis, Characterization, and DNA-Binding Kinetics of New Pd(II) and Pt(II) Thiosemicarbazone Complexes: Spectral, Structural, and Anticancer Evaluation - Simon N. Mbugua; Lydia W. Njenga; Ruth A. Odhiambo; Shem O. Wandiga; Mervin Meyer; Nicole Sibuyi; Roger A. Lalancette; Martin O. Onani (Journal of Chemistry)
In a bid to come up with potential anticancer agents, a class of thiosemicarbazone ligands bearing substituted thiophene were synthesized followed by complexation with various Pd(II) and Pt(II) metal precursors. The ligands (E)-1-((thiophen-2-yl)methylene)thiosemicarbazide (L1), (E)-1-((4-bromothiophen-2-yl)methylene)thiosemicarbazide (L2), and (E)-1-((5-bromothiophen-2-yl)methylene)thiosemicarbazide (L3) were synthesized by condensation reactions and obtained in good yields. Complexation of L1 and L2 with Pd(cod)Cl2 gave C1 (C6H7Cl2N3PdS2) and C2 (C6H6BrCl2N3PdS2), respectively. Complexation of L1 with K2PtCl4 gave C3 (C6H7Cl2N3PtS2), while L3 with K2PtCl2[(PPh)3]2 gave C4 (C24H21BrClN3PPtS2). The structures and coordination for all compounds were established by FTIR, 1H-NMR, 13C-NMR, UV-Vis, elemental analysis, and single-crystal X-ray diffraction studies for ligand L1. Tuning of the spectral and anticancer activity of the compounds was investigated by changing the position of the bromide substituent, metal center, and the σ or π-donor/acceptor strength of the groups surrounding the metal center. The compounds had low to moderate anticancer potency with their spectral and structural properties correlating with the corresponding anticancer activity profiles. DNA binding modes were studied by spectroscopy and were comparable to known DNA intercalators. Structure-activity profiles were evident especially between C1 and C2 differing by the presence of a Br in position 5 of thiophene ring, which caused a remarkable increase in IC50 values, from 14.71 ± 0.016 (C1) to 43.08 ± 0.001(C2) in Caco-2 cells, 1.973 ± 0.048 (C1) to 59.56 ± 0.010 (C2) in MCF-7 cells, 16.65 ± 0.051 (C1) to 72.25 ± 0.003 (C2) in HeLa cells, 14.64 ± 0.037 (C1) to 94.34 ± 0.003 (C2) in HepG2, and 14.05 ± 0.042 (C1) to >100(C2) in PC-3 cells.